ПЕРЕКЛАД ЯК З’ЄДНУЮЧА ЛАНКА МІЖ ДВОМА КАРТИНАМИ СВІТУ (Zaporizhzhia Historical Review, 2021)
In the process of translation two language codes are used, two language cultures are taken into consideration, thus it can be called both interlingual and intercultural communication, although some researchers deny the possibility of such a communication. The reality is unique, whereas the linguistic pictures of the world, i.e. means of its representation in the material sense, differ. It is translation that acts as the connecting link between two pictures of the world. A translator has to find out the common and different features in the perception of a certain notion by the native and non-native speakers of some language and then to use the most adequate means to create an equivalent translation. The necessity is of current importance regarding the tendency to form the international picture of the world.